Field notes contributed by Stephen J. Dinsmore, fall 1995 - Dinsmore, Stephen J.et al (1995)
List of birds and locations contributed by Stephen J. Dinsmore with observers James J. Dinsmore, Jim Sinclair, Hank Zaletel and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1995. Epson - sheet feed/flatbed